(untitled) (Scientific journal of the Fergana State University, 2023)
The article provides brief information on the instructions given by the President of Uzbekistan Shavkat Mirziyoyev, the decisions of the Cabinet of Ministers on pomegranate cultivation, prospects for pomegranate cultivation in Uzbekistan, as well as the creation of new disease-resistant, drought-resistant and high-yielding pomegranate varieties.